Work Family Conflict and Career Progression of Female School Teachers: A Pilot Study - Farooqui, Mahnoor; Alwi, S. Khuram Khan (Pakistan Journal of Humanities and Social Sciences, 2023)
Maintaining a balance between aspects of family and work is pivotal considering the globalization and fast pace trends evolution. For a society to be successful and an individual growth it is vital to have harmony between the dual roles. Individual’s growth and career progression is determined by the factors of family and work. If any conflict between two roles leads to conflict between work and family leading to an ultimate impact on the career progression. The aim of this paper is to validate the research instrument of the relationship of family characteristics, work characteristics, individual related factors, conflict between work and family and career progression of female schoolteachers. Preliminary (pilot) study was conducted to draw the conclusions and have basis for an in-depth analysis of the studied variables. A sample of 60 female schoolteachers was gathered by conducting a questionnaire survey. Childcare, elder care, housework, inflexible working schedule, job-spouse, job-parent were the factors analysed. This preliminary study not only tested the feasibility of the research design but also illuminated areas of potential ambiguity or sensitivity in the questions. The respondents were selected from schools of Karachi, Pakistan. Data analysis was conducted using Smart PLS 4 (SEM) software, based on quantitative analysis of the gathered responses. The results revealed there is a noteworthy association amongst characteristics of family, work family conflict and career progression of female schoolteachers.